Optimizing Strategy for Land-Based Waqf Development in Indonesia - Mutiara Mutiara; Irfan Syauqi Beik; Aslam Mei Nur Widigdo (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. Indonesia waqf’s potential is considered huge. Even though there is an imbalance in utilizing land-based waqf in Indonesia. Most of it are [u1] served to religious-based activity rather than productive action. The aim of this research [u2] is to formulate an optimizing strategy on [u3] land-based waqf development in Indonesia. The priority consideration factor affecting nadhir also be inspected as a strategy formulation basis. ANP (Analytic Network Process) method is equipped in this research. Result [u4] shows that management capability is the priority aspect to nadzhir’s decision in utilizing land-based waqf. Lack of competency becomes the most highlighted problem in that aspect. Fortification towards the regulation is the optimizing strategy in development land-based waqf in [u5] Indonesia.Keywords: Strategy, Optimizing, Land-Based Waqf, Productive Waqf, Institutional Nadzhir.Abstrak. Potensi wakaf di Indonesia sangat besar. Meskipun begitu, terdapat ketimpangan terkait penggunaan tanah wakaf di Indonesia. Sebagian besar tanah wakaf diperuntukan bagi kegiatan yang berbasis ritual keagamaan, dibandingkan dengan kegiatan yang bersifat produktif. Penelitian ini bertujuan pada pembentukan strategi yang optimal dalam pengembangan tanah wakaf di Indonesia. Faktor prioritas pertimbangan yang mempengaruhi nazhir institusi dalam pengelolaan tanah wakaf juga dicari tahu sebagai dasar pembentukan strategi. Metode yang digunakan dalam penelitian ini adalah Analytic Network Process (ANP). Hasil dari penelitian ini menunjukan bahwa yang menjadi prioritas keputusan nazhir dalam pengelolaan tanah wakaf adalah aspek manajemen pengelolaan. Masalah pada aspek manajemen pengelolaan yang menjadi prioritas utama adalah kurangnya kompetensi SDM dengan alternatif solusi peningkatan kompetensi SDM. Penyesuaian dan penyempurnaan regulasi terkait pengelolaan tanah wakaf menjadi strategi yang dinilai paling optimal untuk pengembangan tanah wakaf di Indonesia.Kata kunci: Strategi, Optimalisasi, Tanah wakaf, Wakaf Produktif, Nazhir Institusi. [u1]Is [u2]This research aims to [u3]for  [u4]The result [u5]in the development of land-based